The Struggle for Preventative and Early Detection Networking: The ‘Asabiyya-Driven Structuration of Women’s Breast Cancer in the Arab Region - Luqman, Arwa (Université d'Ottawa / University of Ottawa, 2012)
By 2020, cancer mortality rates are estimated to increase by 180% in Arab countries, where breast cancer is the most common type of cancer. This thesis explores and evaluates the ‘asabiyya-driven structuration (the cohesive force of the group that gives it strength in facing its struggles for progressive reproduction) of cancer agents, government agents, and the World Health Organization agents for breast cancer prevention and early detection in the Arab region. The layers of the philosophical standing from Ibn Khaldûn’s concept of ‘asabiyya and the theoretical foundation of social systems theory, structuration theory, social network analysis, and social capital theory are peeled in order to explore and evaluate the context, constraints, social networks, autopoiesis, and social capital. Utilizing a qualitative research design, this thesis employs content analysis and in-depth interviews, as well as NVivo as a tool for analysis. Data is collected from 122 publications and knowledgeable informants employed by cancer agencies, ministries of health, and World Health Organization offices in Egypt, Jordan, Morocco, and Oman. The findings are divided into the contextual scope of responsibility and resources, the progressive and hierarchal constraining structure, the optimal and weak social networks, the strong and vulnerable shields of autopoiesis, and the presence and absence of social capital momentum, followed by a discussion on the the struggle for structuration against breast cancer. The findings demonstrate that countries with a national cancer control program witness local strengthening ‘asabiyya and ‘asabiyya-driven structuration, while those without a national cancer control program witness weakening local ‘asabiyya. Ultimately, this thesis proposes strategic recommendations to accelerate the regional ‘asabiyya-driven structuration of breast cancer.
Keywords: breast cancer; Arab; World Health Organization; early detection; prevention; government; non-governmental organization; ministry of health; Egypt; Jordan; Morocco; Oman; Eastern Mediterranean Region; 'asabiyya; social network; networking; structuration; social capital; autopoiesis; qualitative; content analysis; in-depth interviews